Immunotherapies for advanced hepatocellular carcinoma - Li-Yang Sun; Li-Yang Sun; Kang-Jun Zhang; Kang-Jun Zhang; Ya-Ming Xie; Jun-Wei Liu; Zun-Qiang Xiao (Frontiers in Pharmacology, 2023)
Primary liver cancer is the second leading cause of tumor-related deaths in China, with hepatocellular carcinoma (HCC) accounting for 80%–90% of these. Since there is a lack of symptoms in the early stages of HCC, a large proportion of patients were identified with unresectable HCC when diagnosed. Due to the severe resistance to chemotherapy, patients with advanced HCC were traditionally treated with systematic therapy in the past decades, and the tyrosine kinase inhibitor (TKI) sorafenib has remained the only treatment option for advanced HCC since 2008. Immunotherapies, particularly immune checkpoint inhibitors (ICIs), have shown a strong anti-tumor effect and have been supported by several guidelines recently. ICIs, for example programmed cell death-1 (PD-1) inhibitors such as nivolumab and pembrolizumab, programmed cell death ligand 1 (PD-L1) inhibitors such as atezolizumab, and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) inhibitors such as ipilimumab, the ICI-based combination with TKIs, and VEGF-neutralizing antibody or systematic or local anti-tumor therapies, are being further studied in clinical trials. However, immune-related adverse events (irAEs) including cutaneous toxicity, gastrointestinal toxicity, and hepatotoxicity may lead to the termination of ICI treatment or even threaten patients’ lives. This review aims to summarize currently available immunotherapies and introduce the irAEs and their managements in order to provide references for clinical application and further research.